Novel Fluorine-18 PET Radiotracers Based on Flumazenil for GABA(A) Imaging in the Brain - Rodnick, Melissa E. (2013)
INTRODUCTION: Two 7-fluoroimidazobenzodiazepines (AH114726 and GEH120348), analogs of flumazenil, were labeled with fluorine-18 and evaluated as alternative radioligands for in vivo imaging of the GABA(A)/benzodiazepine receptor by comparing them to [(11)C]flumazenil in rhesus monkey. METHODS: Radiotracers were prepared from the corresponding nitro-precursors in an automated synthesis module, and primate imaging studies were conducted on a Concorde MicroPET P4 scanner. The brain was imaged for 60 (12 × 5 min frames) or 90 min (18 × 5 min frames), and data was reconstructed using the 3D MAP algorithm. Specificity of [(18)F]AH114726 and [(18)F]GEH120348 was confirmed by displacement studies using unlabeled flumazenil. RESULTS: [(18)F]GEH120348 and [(18)F]AH114726 were obtained in 13–24% yields (end of synthesis) with high chemical (>95%) and radiochemical (>99%) purities, and high specific activities (2061 ± 985 Ci/mmol). The in vivo pharmacokinetics of [(18)F]AH114726 and [(18)F]GEH120348 were determined in a non-human primate and directly compared with [(11)C]flumazenil. Both fluorine-18 radioligands showed time-dependent regional brain distributions that correlated with the distribution of [(11)C]flumazenil and the known concentrations of GABA(A)/benzodiazepine receptors in the monkey brain. [(18)F]AH114726 exhibited maximal brain uptake and tissue time-radioactivity curves that were most similar to [(11)C]flumazenil. In contrast, [(18)F]GEH120348 showed higher initial brain uptake but very different pharmacokinetics, with continued accumulation of radioactivity into the cortical regions of high GABA/benzodiazepine receptor concentrations and very little clearance from the regions of low receptor densities. Rapid washout of both radiotracers occurred upon treatment with unlabeled flumazenil. CONCLUSION: The ease of the radiochemical synthesis, together with in vivo brain pharmacokinetics most similar to [(11)C]flumazenil, support that [(18)F]AH114726 is a suitable option for imaging the GABA(A) receptor.